Observations of two superfast rotator NEAs: 2021 NY1 and 2022 AB. Issue 3 (9th March 2023) - Licandro, Javier; Popescu, Marcel; Tatsumi, Eri; Alarcon, Miguel R; Serra-Ricart, Miquel; Medeiros, Hissa; Morate, David; Tinaut-Ruano, Fernando; de León, Julia
ABSTRACT: In the framework of the visible NEAs observations survey (ViNOS) that uses several telescopes at the Canary Islands observatories since 2018, we observed two superfast rotator NEAs, 2021 NY1 and 2022 AB. We obtained photometry and spectrophotometry of both targets and visible spectroscopy of 2022 AB. Light curves of 2021 NY1 obtained in four different nights between 2021 September 30 and 2021 October 16 return a rotation period P = 13.3449 ± 0.0013 minutes and a light curve amplitude A = 1.00 mag. We found that 2021 NY1 is a very elongated superfast rotator with an axis ratio a / b ≥ 3.6. We also report colours ( g − r ) = 0.664 ± 0.013, ( r − i ) = 0.186 ± 0.013, and ( i − zs ) = −0.117 ± 0.012 mag. These are compatible with an S-type asteroid. The light curves of 2022 AB obtained on 2021 January 5 and 2021 January 8 show a rotation period P = 3.0304 ± 0.0008 min, with amplitudes A = 0.52 and A = 0.54 mag. 2022 AB is also an elongated object with axis ratio a / b ≥ 1.6. The obtained colours are ( g − r ) = 0.400 ± 0.017, ( r − i ) = 0.133 ± 0.017, and ( i − zs ) = 0.093 ± 0.016. These colours are similar to those of the X-types, but with an unusually high ( g − r ) value. Spectra obtained on 2022 January 12 and 2022 January 14 are consistent with the reported colours. The spectral upturn over the 0.4 - 0.6 μ m region of 2022 AB does not fit with any known asteroid taxonomical class or meteorite spectrum, confirming its unusual surface properties.